PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN YANG TERMASUK DALAM LQ 45 Di BURSA EFEK INDONESIA - Rukmana, Ragita Indria; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This main aims of this studyis to testwhether the good corporate governance itindriamechanism which consistsofmanagerial ownership structures, institutional ownership, independent commissioner, and audit quality haveinfluence to the firm value by using Price to Book Value (PBV). The analysis technique is the F statistic testwhich describes whether all independent variables which are included in the model have simultaneous influenceto the dependent variable and the t statistic test which describes how far the influence of one independentvariable individually in explaining the variation of dependent variable with the trust level is 5%. The result ofthe research describes that goodness of fit (model feasibility test) of managerial ownership structures,institutional ownership, independent commissioner, and audit quality have influence to the firm value by usingprice to Book Value (PBV). Meanwhile, partially the managerial ownership has influence to the firm value,institutional ownership has influence to the firm value, and independent commissioner has influence to the firmvalue. Nevertheless, the audit quality does not have any influence to the firm value.Keywords: Price to Book Value (PBV), Management Ownership, Institutional Ownership, IndependentCommissioner,and Audit Quality.